Development of An Interactive Physics E-Module to Foster Problem-Solving Skills in Senior High School Students - Nelfitri Nelfitri; Fahmi Yahya; Hermansyah Hermansyah (Indonesian Journal of STEM Education, 2022)
The low problem-solving ability of students in momentum and impulse topics remains a critical issue in high school physics education, worsened by the lack of interactive learning media. This study aims to: (1) determine the validity level of a problem-solving-oriented interactive physics e-module; and (2) examine students' responses to the e-module. A Research and Development (R&D) approach using the 4-D model was employed, implemented through the Develop stage. Data were collected using expert validation questionnaires and student response questionnaires. The subjects consisted of 10 eleventh-grade Mathematics and Natural Sciences students from a State High School in Sumbawa Regency (2020/2021), selected through purposive sampling. The novelty of this study lies in the explicit integration of Polya's problem-solving indicators into every e-module component, incorporating text, images, animations, simulations, audio, and video within a single digital platform distinguishing it from prior static e-modules. The results showed that: (1) the e-module achieved a validity level in the "very feasible" category at 84.39%; and (2) student responses were categorized as "very good" at 85.16%. Therefore, this interactive physics e-module is suitable as an innovative alternative learning medium.